Palmitoleic acid on top of HFD ameliorates insulin resistance independent of diacylglycerols and alters gut microbiota in C57BL/6J mice - Qijian Liang; Yan Zheng; Fanli Meng; Xiaofan Jiang; Qingcai Zhen; Zhongting Lu; Shixiu Zhang; Lei Du; Hao Wu; Xin Guo (Food Science and Human Wellness)
With the prevalence of obesity and obesity-related metabolic syndrome, such as insulin resistance in recent years, it is urgent to explore effective interventions to prevent the progression of obesity-related metabolic syndrome. Palmitoleic acid is a monounsaturated fatty acid that is available from dietary sources, mainly derived from marine products. Palmitoleic acid plays a positive role in maintaining glucose homeostasis and reducing inflammation. However, it is still unknow the mechanism of palmitoleic acid in ameliorating insulin resistance. Here, we investigated the effects of palmitoleic acid on chow diet (CD)-fed and high-fat diet (HFD)-fed mice, which were fed CD or HFD for 12 weeks before administration. We administrated mice with BSA (control), oleic acid, or palmitoleic acid for 6 weeks on top of CD or HFD feeding. We found that palmitoleic acid only improved glucose homeostasis in HFD-fed obese mice by increasing glucose clearance and reducing HOMA-IR. Further study explored that palmitoleic acid changed the composition of gut microbiota by decreasing Firmicutes population and increasing Bacteroidetes population. In colon, palmitoleic acid increased intestinal tight junction integrity and reduced inflammation. Moreover, palmitoleic acid decreased macrophage infiltration in liver and adipose tissue and increase glucose uptake in adipose tissue. Diacylglycerol (DAG) in tissue (for example, liver) is found to positively correlated with HOMA-IR. HFD enhanced the levels of DAGs in liver but not in adipose tissue in this study. Palmitoleic acid did not reverse the high DAG levels induced by HFD in liver. Therefore, in HFD-fed mice, palmitoleic acid reduced insulin resistance by an independent-manner of DAGs. It might be associated with the beneficial effects of palmitoleic acid on altering the gut microbiota composition, improving of intestinal barrier function, and downregulating the inflammation in colon, liver, and adipose tissue.